Intubation after physiological optimization in the emergency department - Das, Sunil Kumar; Chhantel, Narma; Shah, Ashok Kumar; Tiwari, Umakant; Maharjan, Kripa (Journal of General Practice and Emergency Medicine of Nepal, 2022)
Emergency departments witness all sorts of unprecedented types of patients with respiratory compromise. Airway management must be done expeditiously in dire situations. It’s a well-known fact that patients are not well optimized for intubation as soon as they land up in an emergency. There might have a myriad of comorbidities to be addressed. Amongst various, we have discussed intubation in patients with increased intracranial pressure, patients with shock, patients with acidosis, and patients with respiratory failure. To have a better understanding of the physiological status of patients, reviewed 18 articles, and retrieved a synopsis from the abstract and conclusion. Here we have discussed the physiological optimization of patients based on current recommendation.